Qualidade social da creche: polissemia de múltiplas vozes - Silva, Dilma Antunes (2020)
This research aimed to analyse different perceptions of social quality in the State voices, through official documents, families, teachers, and school managers who act in municipal public nurseries from the eastern region of São Paulo. Due to this aim, we sought to identify what is a good nursery from the perspective of this different actors; to investigate how its perceptions of quality interweave and to highlight the convergences and divergences about the Early Childhood Education. The semi structured interview with a thoughtful character was used in order to collect and to produce information and, afterwards, during the analysis building phase, the content analysis was adopted as methodological inspiration. From the interviews emerged a set of categories which indicate a nursery as a place able of forming to life; an institution essentially educational and complex, who’s the quality is not given a priori, but it depends on multiple factors such as questions regarding “nursery ground” as well as the current political and economical scenario. The research identified that the best child development is favoured by the educative experience in collective environment of life-affirming; emphasizing the nursery’s formative and social character and the importance of the teacher’s work in order to develop the autonomy, affectivity, personality and intelligence of the child. In the context of a good quality nursery socially acknowledged, it is understandable that the education is extended to the parents and the community through actions and practices which amplify the participation and a sense of belonging to the institution in addition to mobilize efforts in order to change the social surrounding. About the complexity and challenges, it was possible to notice the need and urgency of an integration between families and the management team in order to build a childhood school more democratic and fairest; also, it was possible to propose a questioning about the trend in the teacher’s work bureaucratization and massification in the nursery and the coexistence of different formative proposals for the teachers. At this regard, it is suggested that the continuing education during the time of work may focus on the existent demands in the community, coordinating childhood development and learning with political, cultural, social, economics, ethnic, gender, religious matters and so on. Among the main contradictions we may outline: incompatibility between the nursery organization dynamics and its effective democratization through the families and school community real participation; some detachment from the written law and the different tools used in the teaching network and its manifestation in the life of individuals and collectives whom compose and use the education offered by the nursery. As social quality potentiators, despite the discursive inequalities and attitudinal divergences, we could observe: the continuing education centred on the children speaking; the socio-professional and affective relationships in the school environment context; the family integration on the nursery routine; the pedagogical proposal implementation in a no prescriptive way, considering the children as real subjects, rights holders; and, an interlocution between that educative institution and others public spaces/services aiming the confrontation of educational and social inequalities. The research concludes that a good quality education must be coordinated with local and more extensive public policies, aiming to establish the social rights of its actors (children, families, teachers, managers and others school professionals) and the improvement of the population social life quality, as well as the school and its pedagogic political project strengthening